Spatial and temporal variations in Titans surface temperatures from Cassini CIRS observations - Cottini, V; Nixon, C; Jennings, D; De Kok, R; Teanby, N; Irwin, P; Flasar, F (2012)
We report a wide-ranging study of Titans surface temperatures by analysis of the Moons outgoing radiance through a spectral window in the thermal infrared at 19 μm (530 cm -1) characterized by lower atmospheric opacity. We begin by modeling Cassini Composite Infrared Spectrometer (CIRS) far infrared spectra collected in the period 20042010, using a radiative transfer forward model combined with a non-linear optimal estimation inversion method. At low-latitudes, we agree with the HASI near-surface temperature of about 94 K at 10°S (Fulchignoni et al, 2005). We find a systematic decrease from the equator toward the poles, hemispherically asymmetric, of ∼1 K at 60° south and ∼3 K at 60° north, in general agreement with a previous analysis of CIRS data (Jennings et al, 2009), and with Voyager results from the previous northern winter. Subdividing the available database, corresponding to about one Titan season, into 3 consecutive periods, small seasonal changes of up to 2 K at 60°N became noticeable in the results. In addition, clear evidence of diurnal variations of the surface temperatures near the equator are observed for the first time: we find a trend of slowly increasing temperature from the morning to the early afternoon and a faster decrease during the night. The diurnal change is ∼1.5 K, in agreement with model predictions for a surface with a thermal inertia between 300 and 600 J m -2 s -1/2 K -1. These results provide important constraints on coupled surfaceatmosphere models of Titans meteorology and atmospheric dynamic. © 2011 Elsevier Ltd. All rights reserved.